2015
DOI: 10.1111/jace.13847
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yb Concentration on the Optical Properties of CaF2 Transparent Ceramics Codoped with Er and Yb

Abstract: Er, Yb:CaF2 nanoparticles with different Yb concentrations were synthesized by a coprecipitation method using nitrates as raw materials. X‐ray powder diffraction and transmission electron microscopy analysis showed that the nanoparticles were single fluorite phase and the nanoparticle size was found to decrease with increasing Yb concentrations. The obtained nanoparticles were hot‐pressed at 800°C under 30 MPa under vacuum environment to fabricate Er, Yb:CaF2 transparent ceramics. The influence of Yb ion conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Chemically synthesized CaF 2 powders possessing high surface energy and uniform particle size distribution, which are beneficial for the sintering and densifying process. It was reported that the highly transparency fluorite (CaF 2 ) ceramic can be fabricated at 800°C from chemically synthesized powders . As the ball‐milled fluorite powders are much larger than the chemical synthesized CaF 2 powders, optical transparency of polycrystalline ceramics cannot be achieved at 800°C in the study.…”
Section: Resultsmentioning
confidence: 94%
“…Chemically synthesized CaF 2 powders possessing high surface energy and uniform particle size distribution, which are beneficial for the sintering and densifying process. It was reported that the highly transparency fluorite (CaF 2 ) ceramic can be fabricated at 800°C from chemically synthesized powders . As the ball‐milled fluorite powders are much larger than the chemical synthesized CaF 2 powders, optical transparency of polycrystalline ceramics cannot be achieved at 800°C in the study.…”
Section: Resultsmentioning
confidence: 94%
“…The edge of the fundamental absorption band of CaF 2 lies in the vacuum UV at ca. 12 eV, which makes CaF 2 a transparent matrix in the UV-visible-NIR region and makes CaF 2 a unique luminescent matrix in the study of optical properties of luminescent ions 13,32-38. Figure 2 b shows a typical transparent glasslike CaF 2 :Yb ceramic reported by Mortier's group 32.…”
Section: Advantages Of Calcium Fluoride As An Optical Matrixmentioning
confidence: 93%
“…The development of NP-based imaging and therapy has originated a new term; theranostic nanomedicine 9-12. Rare-earth- (RE) doped NPs are particular stars in this category because of the enriched spectral properties of lanthanide ions 13-18. Numerous RE-doped NPs, especially NaYF 4 -related NPs, were synthesized and applied in a wide range of biomedical applications in recent years because of their down/up-conversion luminescence properties 19-24.…”
Section: Introductionmentioning
confidence: 99%
“…Also, enhanced green and red upconversion emissions were reported when concentrations of Er 3+ ions were increased in Er doped LiTaO3 [8]. In general, emission intensities have been found to increase with the increase in concentrations of the Yb and Er ions in the codoped system up to an appropriate dopant concentration [1,8,10]. However, higher concentration can induce cross relaxations between dopants which subsequently reduce the efficiency of the UCL [11].…”
Section: Introductionmentioning
confidence: 97%